Menampilkan Islam Rahmatan lil 'Alamin - Arifuddin Arifuddin (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This research aims to explore the meaning and relevance of Islam Rahmatan lil 'Alamin in the modern era, by focusing on three main pillars: justice, brotherhood, and balance. The research method used in this study is the literature review method. This method involves the analysis and synthesis of various sources of literature related to Islam Rahmatan Lil 'Alamin. Islam Rahmatan lil 'Alamin, which means "Islam as a blessing for the universe", is a central concept in Islam that emphasizes the role of this religion as a bringer of peace, compassion, and goodness for the entire universe.